Actual issues of the theory of environmental law - Соколова, А. К. (Theory and practice of jurisprudence, 2016)
Theoretical issues, connected with the system of principles of such sub-branch of environmental law, as floristic law are researched in this article. Main and primary principles of the latter and its contents are defined